IN VITRO FERMENTATION OF GOAT RUMENT FED WITH FORAGE COMPLETE RATION BASED ON PALM PLANTATION WASTE - Danang Biyatmoko; Tintin Rostini; Irwan Zakir; Arief Hidayatullah (UPT Penerbitan Universitas Jember, 2017)
Palm oil plantation in Kalimantan has potency as a carrying capacity in the development oflivestock, as a source of forage feed source of ruminant livestock. The purpose of thisresearch was to know the digestibility of in vitro complete forage wafer. The method used inthis study was Completely Randomized Design consisting of 5 treatments and 4 replicationsso that there were 20 units of experiments: PT0 = 50% field grass + 50% Legume. PT1 = 50%palm plantation waste + 50% legume; PT2 = 50% palm plantation waste + 50% grass ; PT3 =50% Waste Palm Plantation + 25% Legume + 25% Grass Field. PT4 = 100% Palm Waste.Parameters evaluated were physical properties, wafer quality and characteristics offermentation digestion digestibility of local goat rument fluid. The results showed that theutilization of palm plantation waste with wafer technology had water content, absorbency,density and good texture on PT4 treatment which was 50% of palm plantation waste, 25%lugume and 25% field grass, and also had good nutrition.